Demand for pork and other meats: New estimates and implications for livestock development policy in Vietnam - Toan, N.N.; Lapar, Ma. Lucila; Que, N.N.; Jabbar, M.A.; Tisdell, C.A.; Minot, Nicholas; Staal, Steven J. (2010)
Along with rapid economic growth and increasing affluence, the demand for pork has been increasing steadily; at the same time, consumers have become more demanding with respect to the quality and safety of pork they buy. This paper seeks to examine to what extent changes in consumer income and prices of pork and other meat, are likely to influence the demand for pork. We conduct a demand analysis using the Almost Ideal Demand System (AIDS), of fresh pork and other pork (frozen and processed) and a number of other meat items. We use data from 1,650 households in consumer surveys in Hanoi and Ho Chi Minh city and six rural provinces across Vietnam, selected purposely to represent the geographical and economic diversity of the country. An empirical issue with this type of analysis is the truncated nature of consumption data that induces bias in the estimates. This was addressed by applying the generalized Amemiya two-stage procedure, which is asymptotically more efficient than the Heckman correction method. We find that fresh pork and other pork are relatively inelastic to price and meat expenditure, indicating that pork is not a luxury good within the Vietnamese context. Poultry, egg, beef and seafood appear to be more elastic to meat expenditure. Poultry, beef and fish are statistically shown to be substitutes of pork. Seafood is likely to be a complement of fresh pork but a substitute of other (processed) pork. The findings suggest that pork demand is likely to increase substantially as income rises. On the other hand, consumers also tend to diversify their diet towards other alternatives such as poultry, eggs and beef with increasing affluence. Implications for production and pro-poor livestock development strategy are discussed.